Bacterial communities associated with sugarcane under different agricultural management exhibit a diversity of plant growth-promoting traits and evidence of synergistic effect - Teheran-Sierra, Luis Guillermo [UNESP]; Funnicelli, Michelli Inácio Gonçalves [UNESP]; de Carvalho, Lucas Amoroso Lopes [UNESP]; Ferro, Maria Inês Tiraboschi [UNESP]; Soares, Marcos Antônio; Pinheiro, Daniel Guariz [UNESP] (Elsevier, 2021)
Plant-associated microbiomes have been a target of interest for the prospection of microorganisms, which may be acting as effectors to increase agricultural productivity. For years, the search for beneficial microorganisms has been carried out from the characterization of functional traits of growth-promotion using tests with a few isolates. However, eventually, the expectations with positive results may not be realized when the evaluation is performed in association with plants. In our study, we accessed the cultivable sugarcane microbiome under two conditions of agronomic management: organic and conventional. From the use of a new customized culture medium, we recovered 944 endophytic and epiphytic bacterial communities derived from plant roots, stalks, leaves, and rhizospheric soil. This could be accomplished by using a large-scale approach, initially performing an in planta (Cynodon dactylon) screening process of inoculation to avoid early incompatibility. The inoculation was performed using the bacterial communities, considering that in this way, they could act synergistically. This process resulted in 38 candidate communities, 17 of which had higher Indole-3-acetic acid (IAA) production and phosphate solubilization activity and, were submitted to a new in planta test using Brachiaria ruziziensis and quantification of functional traits for growth-promotion and physiological tests. Enrichment analysis of selected communities has shown that they derived mainly from epiphytic populations of sugarcane stalks under conventional management. The sequencing of the V3-V4 region of the 16S rRNA gene revealed 34 genera and 24 species distributed among the phylum Proteobacteria, Bacteroidetes, Firmicutes, and Actinobacteria. We also observed a network of genera in these communities where the genus Chryseobacterium stands out with a greater degree of interaction, indicating a possible direct or indirect role as a keystone taxon in communities with plant-growth promotion capacities. From the results achieved, we can conclude that the approach is useful in the recovery of a set of sugarcane bacterial communities and that there is, evidence of synergistic action providing benefits to plants, and that they are compatible with plants of the same family (Poaceae). Thus, we are reporting the beneficial bacterial communities identified as suitable candidates with rated potential to be exploited as bioinoculants for crops.
Keywords: Amplicon; Culturomic; PGPB; Saccharum sp.; Symbiosis